Mielopatia associada ao HTLV-I / paraparesia espástica tropical: relato dos primeiros casos em Sergipe - Oliveira, Hélio Araújo (1998)
HTLV-I associated myelopathy/ tropical spastic paraparesis (HAM/TSP) has been decribed in practically all regions of Brazil. The authors present eight clinically defined cases of HAM/TSP, as being the first reported in Sergipe (Northeastern Brazil). All of them were confirmed through ELISA in two examinations, although only two were confirmed by Western Blot. According to clinical/laboratorial investigation protocol, all patients presented involvement of the pyramidal tract with minimal sensory loss and sphincter alteration. The authors call the attention for the endemicity of HTLV-I in the region, whose prevalence amongst blood donors is significant (0.43%).